Helicobacter pylori Management: How to Improve the Therapeutic Confusion in Practice - Nicholas J Talley (Canadian Journal of Gastroenterology)
There appears to be a disconnect between current guidelines for Helicobacter pylori testing and treatment, and clinical practice, including physician beliefs and actual prescribing patterns. In particular, there are markedly different approaches in primary and secondary care, and country- specific differences in eradication therapy for H pylori infection. Although most physicians do not believe that H pylori causes nonulcer dyspepsia, the majority appear to prescribe eradication. Less information is available on the management of H pylori infection and gastroesophageal reflux disease, and more marked differences in attitudes and practice occur in this condition. Even in peptic ulcer disease, where most clinicians both in primary and in secondary care believe H pylori should be eradicated, there is often a breakdown in the translation of this belief into practice. There is also confusion in terms of treatment regimens applied for H pylori eradication. Eradication regimens are less successful in practice than in clinical trials. Furthermore, a sizable proportion of patients with peptic ulcer remain symptomatic despite cure of the ulcer diathesis, which may undermine confidence. Therapeutic confusion about what to prescribe, side effects limiting compliance, bacterial resistance, and socioeconomic factors may all impair therapeutic success with eradication therapy in practice. Unfortunately, it has been well documented that guidelines alone are likely to have little or no impact in practice. Publication in a journal is unlikely to lead to effective implementation in primary care. On the basis of available evidence, clinical behaviour is most likely changed when guidelines are developed by the peer group of clinicians for whom they were intended, are disseminated through a specific educational program, and are implemented by applying, preferably during the consultation, specific reminders.